Crossmodal Connections of Primary Sensory Cortices Largely Vanish During Normal Aging - Henschke, Julia U.; Ohl, Frank W.; Budinger, Eike (Frontiers in Aging Neuroscience, 2018)
During aging, human response times to unisensory and crossmodal stimuli decrease. However, the elderly benefit more from crossmodal stimulus representations than younger people. The underlying short-latency multisensory integration process is mediated by direct crossmodal connections at the level of primary sensory cortices. We investigate the age-related changes of these connections using a rodent model (Mongolian gerbil), retrograde tracer injections into the primary auditory, somatosensory, and visual cortex, and immunohistochemistry for markers of apoptosis (Caspase-3), axonal plasticity (GAP 43), and a calcium-binding protein (Parvalbumin). In adult animals, primary sensory cortices receive a substantial number of direct thalamic inputs from nuclei of their matched, but also from nuclei of non-matched sensory modalities. There are also direct intracortical connections among primary sensory cortices and connections with secondary sensory cortices of other modalities. In very old animals, the crossmodal connections strongly decrease in number or vanish entirely. This is likely due to a retraction of the projection neuron axonal branches rather than ongoing programmed cell death. The loss of crossmodal connections is also accompanied by changes in anatomical correlates of inhibition and excitation in the sensory thalamus and cortex. Together, the loss and restructuring of crossmodal connections during aging suggest a shift of multisensory processing from primary cortices towards other sensory brain areas in elderly individuals.